Simplify, simplify! Brevity, plainness and their complications in American literature and culture: festschrift for Bernd Engler on the occasion of his 65th birthday - Klaiber, Isabell; Scheiding, Oliver; Stievermann, Jan (Beiträge zur englischen und amerikanischen Literatur, 2019)
This volume explores the varieties of the short form in American literature, art, and culture as well as different ideas and aesthetics of simplicity, plainness, and brevity from the 19th century to the present. The contributors discuss how these ideas were translated into widely diverging practices, serving an equally broad spectrum of cultural and political functions. The essays survey a range of media and genres, including short fiction, plays, popular rhetoric, songs, photography, film, and Twitter.
Literaturangaben
Keywords: Engler, Bernd -- 1954-; Festschrift; Engler, Bernd; Kurzepik; Einakter; USA